Case Report: Robot-assisted gait training with the wearable cyborg hybrid assistive limb 2S size in three children with cerebral palsy - Takahashi, Kazushi; Mutsuzaki, Hirotaka; Nakayama, Tomohiro; Kuroda, Mayumi Matsuda; Koseki, Kazunori; Yoshikawa, Kenichi; Nakayama, Junko; Oguro, Haruka; Takeuchi, Ryoko; Mizukami, Masafumi; Watanabe, Hiroki; Marushima, Aiki (Frontiers in Rehabilitation Sciences, 2025)
IntroductionRecently, robot-assisted gait training (RAGT) has attracted attention as a rehabilitation method to efficiently improve walking function. The purpose of this case report is to examine whether there is a change in gait function after RAGT with HAL in children with cerebral palsy (CP).MethodsThree children with CP participated in this study. Case 1 was an 8-year-old boy with Gross Motor Function Classification System (GMFCS) level II. Case 2 involved a 9-year-old girl with a class IV GMFCS. Case 3 was that of a 10-year-old boy with class IV GMFCS. RAGT was conducted once a day for 20 min for a total of 11–12 sessions. Gait was assessed before and after RAGT. We assessed using three-dimensional motion analysis and surface electromyography (sEMG). The sEMG signals were recorded from the bilateral tensor fascia lata, gluteus maximus, semitendinosus, and rectus femoris.ResultsAll cases showed changes in the joint angle and muscle activity in the lower limbs before and after RAGT. In Case 1, the maximum hip extension angle increased from −10.6° to −4.1° at the terminal stance, and the average muscle activity of the gluteus maximus in the right stance phase increased from 22.4% to 30.2%. In Case 2, the maximum extension angle of the left knee joint increased from −43.0° to −26.9°. In Case 3, the maximum hip extension angle increased from −39.9° to −25.9° on the left side and from −35.1° to −18.7° on the right side; the maximum knee extension angle increased from −55.7° to −38.8° on the left side and from −52.1° to −36.9° on the right side.DiscussionA Case 1 had significant hip flexion during gait, but RAGT with HAL emphasized hip extension motion and enabled an efficient gait. As a result, the maximum hip extension angle increased, and the activity of the gluteus maximus muscle in the stance phase increased. Cases 2 and 3 had greater hip and knee joint flexion angles, however increased knee extension angles after RAGT. The increased hip and knee joint extension angles during the stance phase increased the propulsive force propelling the walker forward.